Analisis Faktor Dukungan Keluarga Dan Tingkat Kemandirian Terhadap Tingkat Depresi Lansia - Afrilia Mulyani; Meilia Rahmawati Kusumaningsih; Emi Sutrisminah (Jurnal MID-Z (MIDWIFERI ZIGOT), 2026)
Depression in the elderly is a mental health problem that may reduce quality of life, worsen physical condition, and increase dependency. The main problem is the high risk of depression in the elderly due to lack of family support and low levels of independence. Limited studies have simultaneously examined family support and independence level associated with depression among institutionalized elderly in Indonesia. The purpose of this study was to analyze the relationship between family support and level of independence with depression level among elderly people at the Pucang Gading Elderly Social Service Home, Semarang. This study used a quantitative analytic design with a cross-sectional approach. The sample consisted of 49 elderly respondents selected using purposive sampling. Data were collected using a family support questionnaire, an independence assessment instrument, and a geriatric depression questionnaire. Bivariate analysis was performed using the Spearman rank test with a significance level of 0.05. There was a significant relationship between family support and depression level (p= 0.041; rho= 0,293) and between level of independence and depression level (p=0.047; rho= 0,285). Elderly people with low family support and low independence tend to have higher levels of depression. The results of this study are expected to form the basis for efforts to increase psychosocial support and independence for the elderly in order to reduce levels of depression.